Austerity, economic crisis and children - Koutsampelas, Christos; Andreou, Sofia N.; Papaloi, Evangelia; Dimopoulos, Kostas (My University, 2020)
Cyprus belongs to the group of countries which were hardest hit by the economic recession in Europe. Real GDP sunk by almost 10%, resulting in a large increase in unemployment, wage cuts, reduced household consumption and a rise in poverty and social exclusion. The adverse effects of the crisis were amplified by austerity policies. The aim of the chapter is to provide an overview of the effects of crisis on the wellbeing of families with children and especially of the more vulnerable. Specifically, by using a variety of data sources, we provide an analysis of the impact of crisis on child poverty and on families’ access to affordable childcare and quality education, and briefly assess the role of family policies and schools in mitigating child poverty in a recessionary context.
Keywords: Cyprus; Economic recession; Children; Child poverty